A space-time coding modem for high-data-rate wireless communications. - Naguib, A.F.
This paper presents the theory and practice of a new advanced modem technology suitable for high-data-rate wireless communications and presents its performance over a frequency-flat Rayleigh fading channel. The new technology is based on space-time coded modulation (STCM) with multiple transmit and/or multiple receive antennas and orthogonal pilot sequence insertion (O-PSI). In this approach, data is encoded by a space-time (ST) channel encoder and the output of the encoder is split into N streams to be simultaneously transmitted using N transmit antennas. The transmitter inserts periodic orthogonal pilot sequences in each of the simultaneously transmitted bursts. The receiver uses those pilot sequences to estimate the fading channel. When combined with an appropriately designed interpolation filter, accurate channel state information (CSI) can be estimated for the decoding process. Simulation results of the proposed modem, as applied to the IS-136 cellular standard, are presented. We present the frame error rate (FER) performance results as a function of the signal-to-noise ratio (SNR) and the maximum Doppler frequency, in the presence of timing and frequency offset errors. Simulation results show that for a 10% FER, a 32-state eight-phase-shift keyed (8-PSK) ST code with two transmit and two receive antennas can support data rates up to 55.8 kb/s on a 30-kHz channel, at an SNR of 11.7 dB and a maximum Doppler frequency of 180 Hz. Simulation results for other codes and other channel conditions are also provided. We also compare the performance of the proposed STCM scheme with delay diversity schemes and conclude that STCM can provide significant SNR improvement over simple delay diversity
Keywords: 11.7 dB; 16-QAM.; 180 Hz; 30 kHz; 55.8 kbit/s.; 8-PSK.; IS-136 cellular standard; SNR; TDMA; Channel state information; Data rates; Decoding; Delay diversity; Frame error rate; Frequency offset errors; Frequency-flat Rayleigh fading channel; High-data-rate wireless communications; Interpolation filter; Maximum Doppler frequency; Multiple receive antennas; Multiple transmit antennas; Orthogonal pilot sequence insertion; Performance results; Periodic orthogonal pilot sequences; Signal-to-noise ratio; Simulation results; Space-time channel encoder; Space-time coded modulation; Space-time coding modem; Timing offset errors